Ex vivo evaluation of the accuracy of Raypex® 5 In determining the minor diameter [Raypex® 5'in minör çapin belirlenmesindeki doğruluğunun Ex vivo olarak değerlendirilmesi] - (:unkn) unknown (Cumhuriyet University Faculty of Dentistry, 2011)
Objectives: The aim of this ex vivo study was to assess the accuracy of Raypex® 5 electronic apex locator (EAL) in determining the minor diameter. Methods: Forty extracted maxillary incisors were used in this study. The length between the flat coronal surface and file tip that reached at the major diameter was measured and determined as the reference canal length (RCL). Then the measurements with Raypex® 5 were taken and called as electronic canal length (ECL). The canal instruments were fixed at RCL with flowable composites and four mm. of the apices were shaved and evaluated under stereomicroscope. After the location of the minor diameter was determined on the image of stereomicroscop; the length between coronal reference point and minor diameter were calculated by aid of RCL and determined as minor diameter length (MDL). Then, we compared the measurements of the Raypex® 5 and MDL. Data were analyzed using SPSS 11.5 statistic programme. MDL, ECL and RCL were compared using a paired sample t-test. A p-value equal or less than 0.05 was accepted as statistically significant. Results: The value for ECL (15.22 ± 1.79) was found statistically significantly lower from the value for MDL (15.43± 1.75) (p=0.001). Within the ±0.5 mm the accuracy of Raypex® 5 to determine the minor diameter was calculated as 85%. Conclusions: Although the Raypex® 5 could not determine the minor diameter 100 % under ex vivo experimental conditions; the results of this study clinically could be acceptable.
Keywords: Electronic apex locator; Minor diameter; Working length